circ-0001454 alleviates asthma airway inflammation and remodeling via sponging miR-770-5p and regulating cbl-b - Ruobai Liu; Ruobai Liu; Yilan Song; Yilan Song; Zhiguang Wang; Zhiguang Wang; Longzhu Dai; Longzhu Dai; Qiaoyun Bai; Qiaoyun Bai; Yan Li; Yan Li; et al. (Frontiers in Cell and Developmental Biology)
Bronchial asthma is a chronic inflammatory disease that has long been a severe threat to human physical and mental health. Circular RNAs (circRNAs) and microRNAs (miRNAs) are involved in regulating various processes in asthma. However, the mechanisms by which these molecules influence the pathophysiological processes of asthma through target gene regulation remain unclear. Our study found that inhibition of miR-770-5p alleviated airway inflammation and remodeling in asthmatic mice. Furthermore, bioinformatics analysis revealed that circ-0001454 harbors binding sites for miR-770-5p, acting as a sponge to adsorb miR-770-5p and function as a competing endogenous RNA (ceRNA), thereby negatively regulating the expression of miR-770-5p. Circ-0001454 not only alleviated airway inflammation and remodeling in asthmatic mice, but also participated in modulating the HDM-induced inflammatory response in BEAS-2B cells. It mitigated bronchial epithelial cell inflammatory damage, reduced oxidative stress, apoptosis, and mitochondrial membrane potential loss. Mechanistically, we observed that circ-0001454 partially alleviated the inflammatory damage of epithelial cells caused by miR-770-5p overexpression excessive reactive oxygen species (ROS) production, apoptosis, and mitochondrial membrane potential disruption. Lastly, we found that circ-0001454 targets miR-770-5p and participates in regulating the expression of cbl-b, which in turn modulates the levels of EGFR, AKT1, and MAPK1 proteins, thereby alleviating inflammation in airway epithelial cells. These findings reveal the role of miR-770-5p in asthma, and how circ-0001454, by binding to miR-770-5p and targeting the gene cbl-b, contributes to the attenuation of airway inflammation, reduction of ROS levels, inhibition of apoptosis, and restoration of mitochondrial membrane potential. This regulation of cbl-b, EGFR, AKT1, and MAPK1 suggests new potential therapeutic targets for asthma treatment.